Virtual MultiView Panels for Distant Object Interaction and Navigation in Virtual Reality - Berwaldt, Natan Luiz Paetzhold; Di Domenico, Gabriel; Pozzer, Cesar Tadeu (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
In this paper we present a technique to improve interaction and navigation in virtual reality through the use of multiple virtual cameras projecting their view to windows around the user, expanding the through-the-lens metaphor to a virtual-drone metaphor, and making it possible for users to monitor, and navigate and interact with multiple occluded locations simultaneously using these windows. With this technique, users are able to reach anywhere in the virtual environment in an easy and fast way, without causing discomfort or disorientation. We evaluate the effectiveness of the proposed technique through a user study with two different tasks and assess the task completion performance, user behavior, and preference compared to other known methods.